Impact of tartrazine and curcumin on mineral status, and thyroid and reproductive hormones disruption in vivo - Shakoor, Sadaf; Ismail, A.; Zia-Ur-Rahman, .; Sabran, M. R.; Bekhit, A. E. D. A.; Roohinejad, S. (Universiti Putra Malaysia, 2022)
Endocrine disrupters (EDCs) are naturally occurring or man-made substances that either mimic or obstruct the functions of oestrogens and androgens, thyroid hormones, as well as microminerals in the body. The present work aimed to evaluate the effects of oral administration of tartrazine and curcumin, synthetic and natural dyes, respectively, on thyroid hormones (T3, T4, and TSH), female reproductive hormones (oestrogen, progesterone, LH, and FSH), and minerals (iron, copper, zinc, sodium, potassium, and chloride) in plasma, liver, and kidney of female rats after 15, 30, and 45 d of treatment. The rats were treated with admissible daily intake (ADI) and 10× ADI (9.6 and 96 mg/kg/body weight for tartrazine, 3.85 and 38.5 mg/kg/body weight for curcumin, respectively). Results showed significant changes in thyroid and female reproductive hormones, especially, in the tartrazine-treated groups as compared to the control. Low and high doses of tartrazine and curcumin significantly (p < 0.05) decreased iron, copper, and zinc concentrations in plasma, whereas, the concentrations of sodium and copper in liver and kidney increased. Both tartrazine and curcumin, at ADI and 10× ADI, resulted in lower LH levels after 30 and 45 d of treatment. After 30 d, low and high dose of tartrazine significantly decreased T4, oestrogen, and FSH levels; whereas, progesterone level increased. The results demonstrated that hormone secretion and mineral content in tissues are severely affected at ADI and higher concentrations of tartrazine and curcumin. These observations suggested that lower doses of these dyes might be a safer option for their usage in foods and pharmaceuticals.